Epidemiology and Clinical Characteristics of Congenital Clubfoot in Dhi Qar Governorate, Iraq: A One-Year Descriptive Study - Alshamy, Ihsan Oudah; Alaskary, Murtadha Mutasher; Hasan, Muhanad Flayeh; Kadhium, Noor Jawad (American Journal of Biomedicine and Pharmacy, 2026)
Background: Congenital clubfoot (talipes equinovarus) is one of the most common congenital musculoskeletal deformities worldwide, with a reported incidence of approximately 1–2 cases per 1,000 live births. Early diagnosis and treatment are essential to prevent long-term disability. However, epidemiological data on congenital clubfoot in Iraq remain limited. The aim of this study was to evaluate the incidence, demographic characteristics, and clinical features of congenital clubfoot in Dhi Qar Governorate, southern Iraq. Method: A retrospective descriptive study was conducted including all patients diagnosed with congenital clubfoot who presented to the Nasiriya Clubfoot Center between January and December 2025. Demographic and clinical variables were collected from medical records, including sex, laterality of deformity, type of clubfoot (idiopathic or syndromic), age at first cast, number of casts required for correction, and tenotomy status. The incidence of congenital clubfoot was estimated using the reported number of live births in Dhi Qar Governorate health registry. Results: A total of 62 patients with congenital clubfoot involving 100 affected feet were included in the study. The estimated incidence was approximately 1.05 cases per 1,000 live births. Male patients represented 72.6% of cases, resulting in a male-to-female ratio of 2.6:1. Bilateral deformity was observed in 61% of patients, while unilateral involvement accounted for 39% of cases. The majority of patients were diagnosed with idiopathic clubfoot (95.2%). The mean number of casts required for correction was approximately six casts, and percutaneous Achilles tenotomy was performed in 89% of patients. Conclusion: The incidence and clinical characteristics of congenital clubfoot in Dhi Qar Governorate are comparable to those reported in international literature. These findings provide valuable baseline epidemiological data and highlight the importance of early detection and treatment programs for congenital clubfoot in southern Iraq.